Hip contact force in presence of aberrant bone geometry during normal and pathological gait. Issue 11 (2nd August 2014) - Bosmans, Lode; Wesseling, Mariska; Desloovere, Kaat; Molenaers, Guy; Scheys, Lennart; Jonkers, Ilse
ABSTRACT Children with cerebral palsy (CP) often present aberrant hip geometry, specifically increased femoral anteversion and neck‐shaft angle. Furthermore, altered gait patterns are present within this population. We analyzed the effect of aberrant femoral geometry, as present in CP subjects, on hip contact force (HCF) during pathological and normal gait. We ran dynamic simulations of CP‐specific and normal gait using two musculoskeletal models (MSMs), one reflecting normal femoral geometry and one reflecting proximal femoral deformities. The combination of aberrant bone geometry and CP‐specific gait characteristics reduced HCF compared to normal gait on a CP subject‐specific MSM, but drastically changed the orientation of the HCF vector. The HCF was orientated more vertically and anteriorly than compared to HCF orientation during normal gait. Furthermore, subjects with more pronounced bony deformities encountered larger differences in resultant HCF and HCF orientation. When bone deformities were not accounted for in MSMs of pathologic gait, the HCF orientation was more similar to normal children. Thus, our results support a relation between aberrant femoral geometry and joint loading during pathological/normal gait and confirm a compensatory effect of altered gait kinematics on joint loading. © 2014 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:1406–1415, 2014.